2022
DOI: 10.1371/journal.pone.0273256
|View full text |Cite
|
Sign up to set email alerts
|

Potential SARS-CoV-2 RdRp inhibitors of cytidine derivatives: Molecular docking, molecular dynamic simulations, ADMET, and POM analyses for the identification of pharmacophore sites

Abstract: The RNA-dependent RNA polymerase (RdRp) of SARS-CoV-2 is one of the optimum targets for antiviral drug design and development. The hydroxyl groups of cytidine structures were modified with different aliphatic and aromatic groups to obtain 5´-O-acyl and 2´,3´-di-O-acyl derivatives, and then, these derivatives were employed in molecular modeling, antiviral prediction, molecular docking, molecular dynamics, pharmacological and POM studies. Density functional theory (DFT) at the B3LYP/6-31G++ level analyzed bioche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 66 publications
(65 reference statements)
1
14
0
Order By: Relevance
“…Sixteen-proton multiples at δ 1.29 {CH 3 (C H 2 ) 8 (CH 2 ) 2 CO-} and three-proton multiples at δ 0.90 {C H 3 (CH 2 ) 10 CO-} were also seen. These findings rationalize the appearance of a lauroyl group in position 2 as depicted by the deshielding of the C-2 proton from its common value (~4.00) [ 39 , 40 ] in the initial diol ( 2 ) to δ 4.83 (as dd, J = 3.7 Hz, and 9.7 Hz). The 13 C-NMR spectrum also displayed the appearance of a lauroyl group following the prospective resonance peaks: δ 174.61 {CH 3 (CH 2 ) 10 C O-}, δ 34.18, 31.94, 29.64 (×2), 29.50, 29.31, 29.30, 29.02, 24.97, 22.73 {CH 3 ( C H 2 ) 10 CO-} and δ 14.17 { C H 3 (CH 2 ) 10 CO-}.…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…Sixteen-proton multiples at δ 1.29 {CH 3 (C H 2 ) 8 (CH 2 ) 2 CO-} and three-proton multiples at δ 0.90 {C H 3 (CH 2 ) 10 CO-} were also seen. These findings rationalize the appearance of a lauroyl group in position 2 as depicted by the deshielding of the C-2 proton from its common value (~4.00) [ 39 , 40 ] in the initial diol ( 2 ) to δ 4.83 (as dd, J = 3.7 Hz, and 9.7 Hz). The 13 C-NMR spectrum also displayed the appearance of a lauroyl group following the prospective resonance peaks: δ 174.61 {CH 3 (CH 2 ) 10 C O-}, δ 34.18, 31.94, 29.64 (×2), 29.50, 29.31, 29.30, 29.02, 24.97, 22.73 {CH 3 ( C H 2 ) 10 CO-} and δ 14.17 { C H 3 (CH 2 ) 10 CO-}.…”
Section: Resultssupporting
confidence: 75%
“…The present work has two objectives which are mainly the synthesis of a series of derivatives by substituting the hydroxyl group (-OH) of methyl 4,6- O -benzylidene-α- d -glucopyranoside (MBG) with various acyls groups (including aromatic and heteroaromatic group), followed by an exploration of the characterization of their physicochemical and biological properties using in vitro and in silico methods. It is important to mention that employing the in silico approach could help to provide insightful information for complicated biological systems [ 38 , 39 , 40 ]. After establishing the structure and purity of these new derivatives by employing spectroscopic and chromatography methods, their antibacterial and antifungal activities were evaluated in vitro against five collected strains.…”
Section: Introductionmentioning
confidence: 99%
“…In their research study, Kawsar et al [192] . subjected fourteen cytidine compounds to modification using various aliphatic and aromatic chains ( 127 – 140 ), as shown in Figure 12.…”
Section: Computational Studies Revealing Potential Sars‐cov‐2 Main Pr...mentioning
confidence: 99%
“…Analysis based on molecular dynamics simulations. A. RMSD, B. RMSF and C. RoG (radius of gyration) [192].…”
mentioning
confidence: 99%
“…The pharmacophore sites exhibiting antifungal properties (O1 δ− ---O2 δ− ) have been validated through atomic charge calculations of compounds. It was observed that these compounds exhibit a greater degree of e cacy as antifungal and antiviral agents than antibacterial agents (Munia et al 2022;Kawsar et al 2022Kawsar et al , 2023.…”
Section: Molinspiration Analysismentioning
confidence: 99%